Carbon storage of medium-sized tree: a case study on Dillenia collection in Purwodadi Botanic Garden - Ridesti Rindyastuti (The East Java Biological Society, 2017)
Dillenia is a medium-sized tree which has high species diversity in tropical regions especially in Southeast Asia. Dillenia in Purwodadi Botanic Garden are collected from native habitats in Java, Kalimantan, Sulawesi and Papua which planted on the area of 17 x 55 m2. The purpose of this re-search is to study the above ground carbon storage in Dillenia collection in Purwodadi Botanic Garden. Carbon storage estimation was established by measuring stem carbon stocks from plant collections with plant age ranging between 12-30 years. Twelve years old collection contributed carbon storage of 7.35 tonnes/ha for D. sumatrana. Twenty years old species had the lowest carbon storage of 2.17 kg/plant for D. serrata and the highest of 51.9 kg/plant for D. auriculata with a range of carbon storage of 3.47 to 41.072 tonnes/Ha. Thirty years old plant contributed 39.465 kg/plant and carbon storages of 63.14 tonnes/ha for D. serrata and 135.59 kg/plant and 216.94 tonnes/ha for D. philipinensis. Overall, Dillenia collections in Pur-wodadi Botanic Garden contributed 793.94 kg carbon storages, store carbon on average of 30.54 kg/plant and 46.46 tonnes/ha. The increase of carbon storage in the second 10 years was higher than in the first 10 years. It indicated that Dillenia had growth strategy in the early growth then alocated more mass after 10 years. Carbon storage of Dillenia was high and different in age. D. serrata, D. papuana and D. auriculata are recommended species as a priority in planting trees based on carbon sink.